Dampak Kegiatan Pelatihan office Terhadap Peningkatan Mutu Siswa Sekolah Dasar Dalam Mendukung Pembalajaran - Alief Fathul Habibie; Ahmad Fajar Awalushihab; Pazri; Silfia Septiani; Syawaluddin Nasution (Forum Kerjasama Pendidikan Tinggi, 2023)
Information and communication technology (ICT) literacy and mastery of information interactive media are obligations that must be carried out by an educator in the era of the cessation of information and technology development which is growing rapidly in parts of the world. However, seeing the conditions that occurred at SD Negeri 105343 Ramunia I/II, they did not yet have access and it could be said that they lacked basic education in the field of technology and information. The school does not have teaching staff capable of information and communication technology in it. Apart from that, the school also does not have supporting access sources such as classrooms and computer laboratories. So it was on this basis and conditions that made it an innovation for us as group 48 participants (KKN) to help and become an extension of the teaching staff at SD Negeri 105343 Ramunia I/II. One of them is a work program launched with the theme of basic training on the Science and Technology aspects of measuring community understanding of (IT). This activity was realized by students from the Faculty of Science and Technology UIN North Sumatra by providing basic Microsoft Word and Powerpoint training for fifth and sixth grade students at SD Negeri 105343. challenges and experiences for us as creators of these activities. Of course, with the basic Microsoft Word and Powerpoint training activities, it is hoped that later it will be able to help students, especially grades five and six, in preparing for computer-based exams, then increase their understanding and knowledge in computerized systems, and provide motivation as well as enthusiasm to be able to use technology wisely. and careful.